PROGRAMA DE MELHORIA DO ACESSO E QUALIDADE DA ATENÇÃO BÁSICA DO SUS (PMAQ-AB): análise da estrutura das unidades básicas de saúde do Maranhão - Cavalcante, Vânia Cristina Reis (2014)
Introduction: a review of the structure of health services is an important tool in the management practice. Objective: To analyze the structure of the Basic Health Units (BHU) of Maranhão (MA), according to adherence (PMAQ-AB) Program for Improving Access and Quality of Primary Care in the NHS. Methods: We developed a cross-sectional ecological study. Data were collected in 2012. We evaluated all of the 217 municipalities of UBS MA, subdivided into two groups: those who joined the PMAQ - AB (G1) and those who did not adhere (G2). Differences between groups were tested by chi- square test (alpha = 5 %). Organizational resources, infrastructure / ambience and strategic elements, subdivided into categories, subcategories and indicators: four components of the structure were evaluated. Results: 1,879 UBS were evaluated. Organizational: most teams was the Family Health Strategy (FHS) with oral health team (ESB), reported working five days a week, two shifts, but few listened to alternative schedules. Reported availability of automotive vehicles. The average FHS with ESB (p < 0.001) and parameterized teams (p< 0.001) was higher in G1 than in G2. Resources: There was a shortfall in basic professional teams and expanded in both groups. There was still a deficit of general and dental equipment, dental supplies, printed materials and for rapid testing. All the routine immunization schedule was always available in only 92 (4.9%) UBS. But there was good availability of consumer medicines in general and in most UBS materials. The availability of resources was significantly better in G1 (p < 0.001). Infrastructure / ambience: there was inadequate physical plant, ambiance, and accessibility signage in most UBS. The physical plant conditions and ambience were better in G1, since the electrical and hydraulic conditions in G2 (p < 0.001). Strategic elements: telehealth, complementary and integrative praticas herbal practically were not offered in MA. Conclusion: the structure of UBS in MA is inadequate, except in the organizational component. The UBS joined the PMAQ-AB have better structure than the others. This demonstrates the possibility of interference in the work processes and the quality of primary care.